The 21st-Century Voice: Contemporary and Traditional Extra-Normal Voice - Edgerton, Michael Edward (Rowman & Littlefield Publishers, 2015)
In The 21st-Century Voice: Contemporary and Traditional Extra-Normal Voice, Michael Edward Edgerton considers contemporary vocal techniques within an acoustic and anatomical framework. Throughout, he proposes new directions for vocal exploration. Much more than a historical treatise on 20th-century masterworks or vocal science, The 21st-Century Voice explores experimental methods of sound production, offering a systematic series of approaches and methods for assessing, engaging, and, in some instances, overcoming the assumed limits of vocal singing. Appearing a decade after the publication of the first edition, this second editiondraws on and advances our current understandings of voice production. Divided into four parts—air flow, source, resonance/articulation, and heightened potentials—Edgerton considers crucial matters affecting vocal production, such as Registral challenges Filtering Airflow modification Combinatorial, multiphonic principles Extreme voice possibilities Multidimensional vocal issues With more than 250 illustrations, 150 associated audio tracks, an extended appendix on voice science, a glossary of key terms, and lists of representative compositions, The 21st-Century Voice will appeal to composers and performers interested in exploring the ever-broadening range of vocal possibilities. Its engagement with the complexities of vocal production should also be relevant to students and scholars of voice science, acoustics, linguistics, computer modeling, and more.